Oxime ligands for Pd catalysis of the mizoroki–heck reaction, Suzuki–Miyaura coupling & annulation reactions - Bangar, Pronnoy G.; Nahide, Pradip D.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Synthetic Communications, 2021)
AbstractMonodentate and bidentate chelating oximes are readily available ligands for the Pd catalysis of the Mizoroki–Heck reaction and the Suzuki coupling. High yields were obtained in the Suzuki coupling in aqueous dioxane with TBABr as additive. The oximes can be easily synthesized from the corresponding ketones or aldehydes and thus provide a very large number of nitrogen-based ligands. They have the advantage of not undergoing oxidative degradation, common for phosphine ligands. Chelating oximes with Pd(OAc)2, activate aryl iodides to give high yields of the substitution products in the Mizoroki–Heck reactions as well as the Suzuki coupling. Acetophenone oxime ligand with Pd(OAc)2, catalyzed the reaction of aryl iodides with 1,2-disubstituted alkenes in moderate to high yields. As a test example, the LaRock indole annulation and synthesis of isocoumarin were achieved with acetophenone oxime ligand and Pd(OAc)2 in high yields.